Impacts of El Niño Diversity on Tropical Cyclone Activity in the Bay of Bengal - Lakshani, W. A. E.; Zhou, Wen; Cheung, Paxson K. Y. (Frontiers in Earth Science, 2022)
This study investigates the variation in large-scale parameters associated with two types of El Niño and their impact on tropical cyclone (TC) activity over the Bay of Bengal (BoB) from 1980 to 2019. The Genesis Potential Index (GPI)-based quantitative evaluation was conducted to compute the relative contribution of ENSO and El Niño flavor–associated large-scale parameters. Relationship between the GPI and ENSO in the primary TC peak season (October–November; OND) exhibits a distinct meridional pattern over southwestern to northeastern parts of the BoB. Moreover, the results show that ENSO-modulated vertical wind shear (VWS) term (relative humidity; RH term) contributes the most to enhancing (suppressing) the GPI over the southwestern (northeastern) BoB during the primary TC peak season. The GPI exhibits a significantly positive (negative) dipole pattern with EP El Niño in the southern (northern) BoB, while CP El Niño shows a southwestern (positive)–northeastern (negative) meridional pattern. The increased GPI in the southern BoB with EP El Niño is due mainly to the VWS term, while RH term makes a minimal contribution. Similarly, during CP El Niño, VWS term contributes the most to the enhancement of the GPI, while the smallest contribution is from potential intensity (PI) term. Moreover, this study reveals that the thermodynamic (RH) factor is crucial in reducing TC genesis during CP El Niño in the northeastern BoB. On the other hand, the dynamic (VWS) and thermodynamic (RH) terms are almost equally important for suppressing TCs over the northern BoB in EP El Niño.Analysis of the secondary TC peak season (April–June; AMJ) demonstrates that CP El Niño and EP El Niño induce an increase and decrease in the GPI in the southern BoB mainly due to the dynamic factor (VWS term) and thermodynamic factor (RH term), respectively. On the other hand, TCs in AMJ are more favorable to occur in the south of BoB during CP El Niño events. The two types of El Niño-associated physical mechanisms are consistent with the diagnosed GPI changes, emphasizing the vital role of both EP and CP El Niño in influencing thermodynamic and dynamic parameters related to TC genesis over the BoB. Thus, the association of CP and EP El Niño with the GPI provides a valuable platform for studying El Niño–generated TC impacts over the BoB.